VEHICLE TRACKING SYSTEM INVOLVED DROWSINESS DETECTION SYSTEM USING BUZZER & VIBRATION SENSOR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Driver impairment due to drowsiness is known to be a major contributing factor in many motor vehicle crashes. More than 30% of the road accidents are caused by the fatigue of the driver. At present, there are various drowsiness detection systems available in the market. These systems are implemented using any one of the various implementation techniques such as detection of any behavioural pattern, changes in physiological conditions, or vehicular motion. Consequently, the accuracy of such systems has been found to be low..The paper is built around MCU. Here we are using eye blink sensor. By default the vehicle will be in running condition. During this time if the person closes the eyes automatically the vehicle will be in halt condition, the updated message will be displayed on the 16x2 LCD. The Position will be messaged using GPS and GSM respectively interfaced to the controller. A vibrator is also interfaced so that the driver will be alerted and can drive safely. This paper uses regulated 5V, 500mA power supply. 7805 three terminal voltage regulator is used for voltage regulation. Bridge type full wave rectifier is used to rectify the ac output of secondary of 230/12V step down transformer.